The influence of Organizational Communication, Work Motivation, and Self-Efficacy on Employee Performance in PT Angkasa Pura Logistik Semarang - Putri Dirgantara Sakti; Putut - Haribowo; Makmun - Riyanto (Politeknik Negeri Semarang, 2020)
The aspect of human resources or employees is an important factor that must be considered in the company. Human resources are the main assets for the company as active actors in various activities in the organization. Many companies provide logistic services such as warehousing, transportation services, freight services, etc. One company that used the service of logistic provider is PT Angkasa Pura Logistik Semarang. Due to the large number of logistic companies, PT Angkasa Pura Logistik Semarang needs to improve its employees' performance to compete in the logistics industry. Therefore, they must pay more attention to organizational communication, work motivation, and self-efficacy of their employees. The purpose of this research is to analyze the influence of organizational communication, work motivation, and self-efficacy on employee performance in PT Angkasa Pura Logistik Semarang. The research model was used multiple linear regression and SPSS 25. The sampling method used was simple random sampling. The questionnaire was distributed to 50 samples of staff in PT Angkasa Pura Logistik Semarang. The results showed that organizational communication had a positive and significantly influenced employee performance with a significant value of 0.011 < 0.025 and the t value of 2.640 > t table 2.01290. The variable of work motivation had a positive and significant influence on employee performance with a significant value of 0.013 < 0.025 and the t value of 2.583 > t table 2.01290. The self-efficacy variable had a positive and significant influence on employee performance with a significant value of 0.023 < 0.025 and the t value of 2.360 > t table 2.01290